Schloss Weilburg at Baden bei Wien - Meyer, Joseph, 1796-1856 (author):::Creator:::::::::::: (Hildburghausen; Kunstanst d. Bibliographisches Institut, 2020)
Engraving of the Schloss Weilburg at Baden bei Wien. Includes 3 pages of text from the book.